2023
DOI: 10.1111/epp.12904
|View full text |Cite
|
Sign up to set email alerts
|

Pale tussock moth, Calliteara pudibunda (Linnaeus, 1758) (Lepidoptera; Erebidae) with a focus on its situation in Türkiye

Abstract: Calliteara pudibunda is a univoltine, polyphagous and native species producing periodic outbreaks which have been recorded only in Europe so far. Its larvae feed on the foliage of beech, oak and several other deciduous and coniferous trees. It is very widespread in Eurasia. In Europe, it is found between the 34th and 60th parallels. In Türkiye, it occurs mainly in coastal regions. Its outbreak range had been thought to be confined between the 48th and 57th parallels in Europe until the last two decades when ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Another important species, the pale tussock moth, Calliteara pudibunda is native to the Northwestern Palearctic region. It has been detected in the provinces of Artvin, Balıkesir, Bursa, Düzce, Giresun, Hatay, İstanbul, Kütahya, Malatya, Sakarya, Samsun, and Yalova in Türkiye (Ipekdal & Avcı, 2023). It caused damage on alder and birch trees in 2005 in Türkiye (Göktürk & Aksu, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important species, the pale tussock moth, Calliteara pudibunda is native to the Northwestern Palearctic region. It has been detected in the provinces of Artvin, Balıkesir, Bursa, Düzce, Giresun, Hatay, İstanbul, Kütahya, Malatya, Sakarya, Samsun, and Yalova in Türkiye (Ipekdal & Avcı, 2023). It caused damage on alder and birch trees in 2005 in Türkiye (Göktürk & Aksu, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…It caused damage on alder and birch trees in 2005 in Türkiye (Göktürk & Aksu, 2005). C. pudibunda is a defoliating species that consumes leaves or needles (Ipekdal, 2022;Ipekdal & Avcı, 2023). Sarıkaya et al (2019) reported the outbreak occurred in oriental beech (Fagus orientalis Lipsky) forests of İnegöl (Bursa), Türkiye between 2018 and 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation